Prevalence and Impact of Hyponatremia in Patients With Coronavirus Disease 2019 in New York City. Issue 12 (December 2020) - Frontera, Jennifer A.; Valdes, Eduard; Huang, Joshua; Lewis, Ariane; Lord, Aaron S.; Zhou, Ting; Kahn, D. Ethan; Melmed, Kara; Czeisler, Barry M.; Yaghi, Shadi; Scher, Erica; Wisniewski, Thomas; et al.
Abstract : Objectives: Hyponatremia occurs in up to 30% of patients with pneumonia and is associated with increased morbidity and mortality. The prevalence of hyponatremia associated with coronavirus disease 2019 and the impact on outcome is unknown. We aimed to identify the prevalence, predictors, and impact on outcome of mild, moderate, and severe admission hyponatremia compared with normonatremia among coronavirus disease 2019 patients. Design: Retrospective, multicenter, observational cohort study. Setting: Four New York City hospitals that are part of the same health network. Patients: Hospitalized, laboratory-confirmed adult coronavirus disease 2019 patients admitted between March 1, 2020, and May 13, 2020. Interventions: None. Measurements and Main Results: Hyponatremia was categorized as mild (sodium: 130–134 mmol/L), moderate (sodium: 121–129 mmol/L), or severe (sodium: ⩽ 120 mmol/L) versus normonatremia (135–145 mmol/L). The primary outcome was the association of increasing severity of hyponatremia and in-hospital mortality assessed using multivariable logistic regression analysis. Secondary outcomes included encephalopathy, acute renal failure, mechanical ventilation, and discharge home compared across sodium levels using Kruskal-Wallis and chi-square tests. In exploratory analysis, the association of sodium levels and interleukin-6 levels (which has been linked to nonosmotic release of vasopressin) was assessed. Among 4, 645 patient encounters, hyponatremia (sodium < 135 mmol/L) occurred in 1, 373 (30%) and 374 of 1, 373 (27%) required invasive mechanical ventilation. Mild, moderate, and severe hyponatremia occurred in 1, 032 (22%), 305 (7%), and 36 (1%) patients, respectively. Each level of worsening hyponatremia conferred 43% increased odds of in-hospital death after adjusting for age, gender, race, body mass index, past medical history, admission laboratory abnormalities, admission Sequential Organ Failure Assessment score, renal failure, encephalopathy, and mechanical ventilation (adjusted odds ratio, 1.43; 95% CI, 1.08–1.88; p = 0.012). Increasing severity of hyponatremia was associated with encephalopathy, mechanical ventilation, and decreased probability of discharge home (all p < 0.001). Higher interleukin-6 levels correlated with lower sodium levels ( p = 0.017). Conclusions: Hyponatremia occurred in nearly a third of coronavirus disease 2019 patients, was an independent predictor of in-hospital mortality, and was associated with increased risk of encephalopathy and mechanical ventilation. Abstract : Supplemental Digital Content is available in the text.